Interpretation of the glacial lake outburst floods database in relation to climatic conditions in different world regions - Matouš Kovanda (Acta Universitatis Carolinae Geographica)
This article investigates the response of glacial lake outburst floods (GLOFs) to climatic conditions since the beginning of the 20th century and during individual seasons based on the data from the publicly available online database recording past GLOFs worldwide. All recorded GLOFs were classified into the regions of Alaska, Western Canada and USA, Central Andes, Southern Andes, Iceland, Scandinavia, Alps, Caucasus, Tian Shan, Central Asia I (west), Central Asia II (east), and New Zealand. In each of these regions, the influence of temperature and precipitation on the frequency of glacial flood occurrences was investigated. It was established that GLOFs occur mainly during the summer months and air temperature is their main triggering factor. Since the frequency of GLOFs is influenced by both temperature and precipitation, a gradual increase in the frequency of GLOFs is expected because of global warming, although the relative importance of each factor will vary across regions.